Regulatory T cells stimulate B7-H1 expression in myeloid-derived suppressor cells in ret melanomas - Fujimura, Taku; Ring, Sabine; Umansky, Viktor; Mahnke, Karsten; Enk, Alexander (The journal of investigative dermatology, 2012)
Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of cells, and they promote an immunosuppressive environment in tumor-bearing hosts. To characterize MDSCs in melanoma, we examined the expression of inhibitory B7 molecules by CD11b+Gr1+ cells isolated from mice with transplantable ret tumors. B7 molecules were expressed on CD11b+Gr1+ cells, which also expressed CD124 and inducible nitric oxide synthase, thus verifying their relation to MDSCs. In developing melanomas, CD11b+Gr1+ cells express only low levels of B7-H1. In contrast, B7-H1 is upregulated in large tumors, and functional analysis demonstrates that CD11b+Gr-1+ cells suppress the proliferation of CD4+ T cells through B7-H1. Depletion of regulatory T cells (Tregs) significantly downregulated the expression of B7-H1, B7-H3, and B7-H4 on MDSCs and reduced tumor growth, indicating a concerted immunosuppressive activity of Tregs and MDSCs. No differences in the suppressive function of MDSCs between CD25-depleted and non-depleted mice were recorded. Instead, tumor-derived MDSCs from Treg-depleted hosts produced less IL-10 and more IFN-γ as compared with Treg-harboring mice. These studies indicate that Tregs in tumors not only suppress effector T cells directly, but also modify the phenotype of tumor-infiltrating CD11b+ cells to express inhibitory B7-H molecules and to produce IL-10.